Comparison of two sedation protocols for diagnostic radiography in dogs with hip dysplasia - Suzane Lilian Beier; Marcos Paulo Antunes de Lima; Felipe Gaia de Sousa; Renata Andrade Silva; Natália Fagundes; Milena Fascina Bovi; Renato Cesar Sacchetto Tôrres (Veterinary and Animal Science, 2023)
Hip dysplasia is an alteration with a high incidence in large dogs. The aim of the study was to compare the association of xylazine or dexmedetomidine with fentanyl for radiography with joint distractor for the diagnosis of hip dysplasia. Fifteen healthy dogs, German Shepherd and Belgian Shepherd, were randomly submitted to treatments 0.2 mg/kg xylazine + 2.5 µg/kg fentanyl (XF) or 2 µg/kg dexmedetomidine + 2.5 µg/kg fentanyl (DF), intravenously. HR, f, SAP, MAP, DAP and TR were evaluated at intervals of 5 min before and after the administration of treatments; pH, PaCO2, PaO2, BE, HCO3−, SaO2, Na+, K+ and Hb at 5 and 15 min after treatment administration; and the quality of sedation at intervals of 5 min after administration of treatments. Latency, duration, and recovery times were also compared. The HR values showed a significant reduction in both groups, as well as pH, PaCO2, PaO2 and SaO2. Latency, duration and recovery times, and quality of sedation did not differ statistically between groups. Xylazine and fentanyl or dexmedetomidine and fentanyl combinations provide adequate sedation and analgesia for performing diagnostic radiographic procedures for hip dysplasia. However, oxygen supplementation is recommended to increase protocol safety.